Deriving technology indicators from corporate websites: A comparative assessment using patents - Sebastian Heinrich (ETH Zurich, KOF Swiss Economic Institute, 2023)
This paper investigates the potential of indicators derived from corporate websites to measure technology related concepts. Using artificial intelligence (AI) technology as a case in point, I construct a 24-year panel combining the texts of websites and patent portfolios for over 1,000 large companies. By identifying AI exposure with a comprehensive keyword set, I show that website and patent data are strongly related, suggesting that corporate websites constitute a promising data source to trace AI technologies.
hdl:20.500.11850/623739
Keywords: C81; O31; O33; 330; corporate website; patent portfolio; technology indicator; text data; artificial intelligence